Identity check: documenting the type specimens of historical Malagasy wolf spiders (Araneae: Lycosidae) - Sherwood, Danniella; Jäger, Peter (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
This work aims to digitize and disseminate knowledge on historical specimens of Malagasy lycosids, as a foundation for future researchers intending to undertake a comprehensive review of this fauna. The types of Arctosa atroventrosa (Lenz, 1886), Geolycosa nossibeensis (Strand, 1907), Hippasosa fera (Strand, 1907), and Trochosa urbana hova Strand, 1907 were examined, figured, and their taxonomic identities discussed herein. Arctosa atroventrosa is proposed as a nomen dubium. Geolycosa nossibeensis is clearly misplaced in Geolycosa Montgomery, 1904 and is transferred to Trochosa C. L. Koch, 1847 as Trochosa nossibeensis comb. nov. Likewise, H. fera is a valid species but is misplaced in Hippasosa Roewer, 1960 and does not belong to this genus. Trochosa urbana hova, recently synonymised with the nominal species is confirmed in its current taxonomic placement. Lycosa madagascariensis Vinson, 1863 is treated as a species inquirenda as the types cannot be located but the mention of specific localities in Madagascar could allow future workers to designate a neotype to recognise this species. Lycosa signata Lenz, 1886 is treated as a valid species, although a neotype designation will be required in future as the holotype was destroyed as a result of bombing raids on the Museum of Lübeck during the World War II and its vulva never previously illustrated.
Keywords: Morphology; Taxonomy; Arctosa; Hippasosa; Lycosa; Trochosa